The transmission of euro area monetary policy to financially euroised countries - Isabella Moder (European Central Bank (ECB), 2021)
This paper provides a comprehensive analysis of the interest rate pass-through of euro area monetary policy to retail rates outside the euro area, contributing to the literature on the consequences of unofficial financial euroisation and on the transmission channels of monetary policy spillovers. The results suggest that in the long run, more than one third of all euro retail rates in euroised countries of central, eastern and south-eastern Europe (CESEE) are linked to the euro area shadow rate. Compared to euro area monetary policy, the share of cointegration of the domestic monetary policy rate is lower, suggesting that domestic central banks in euroised countries with independent monetary policy can only partially control the "euro part" of the interest rate channel. Furthermore, euro area monetary policy shocks are fast and persistently transmitted into euro retail rates outside the euro area, which constitutes an additional channel of international shock transmission.
Keywords: C22; C32; E43; E52; F42; 330; monetary policy transmission; international monetary policy spillovers; unofficial financial euroisation; EU integration